Legal Protection for Creditors Against the Assets of Bankrupt Debtors Confiscated as Evidence - Adipradana, Nugroho; Adi, Rianto; Ginting, Jamin (Global Legal Review, 2024)
The uncertainty of the status of affiliated bankruptcy debtors as evidence of criminal offenses is a classic problem that until now has not found an alternative legal solution. When a bankruptcy debtor is proven to have committed a criminal offense, resulting in the debtor's assets becoming evidence seized by the criminal, the curator will experience difficulties in the process of liquidating the debtor's assets. On the one hand, the prosecutor's office has the authority to confiscate the assets of the debtor (defendant), as well as the curator who has the authority to liquidate. The emergence of these two types of seizure is certainly intended to provide legal certainty and legal protection for the community. However, in its implementation, when the two types of seizure clash, the aspects of certainty and justice for the community will not be achieved. Therefore, it is necessary to establish regulations that can bridge or unravel the problem of attraction of seizure objects between the curator and the prosecutor's office. The research method used in this research is juridical-normative by using several research approaches, namely statute approach and conceptual approach. The use of statute approach in the research is intended to provide an overview of the construction of bankruptcy and criminal law so as to hamper the process of liquidation of bankruptcy assets. While the use of conceptual approach is intended as a basis for thinking to reconstruct the legal construction so as to create harmonious and synchronous bankruptcy and criminal regulations and can provide certainty and justice for the legal protection of creditors.